ANALISIS RANTAI NILAI PADA UMKM SUSU KEDELAI DI KOTA DENPASAR - Samuel P.T, Alexander; Suryawan Wiranatha, A.A.P. Agung; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
The study, entitled "Value Chain Analysis on the SME of Soybean Milk in Denpasar" aimed: (1) to analyze the value-added processing and value-added marketing on a small industrial processing of regular soybean milk (imported soybean) and the edamame soybean in Denpasar City area; (2) To analyze the marketing distribution channels of soybean milk products in Denpasar; and (3) to determine the soybean milk marketing distribution channels that generate the highest added value. This research used Added Value Analysis (Hayami et al., 1987) to calculate the value added in the processing and marketing in the process of soy milk products that use raw materials of edamame soybeans and regular soybean (imported material). The results of the research concluded that the value-added processing on edamame soy milk products was Rp. 72.810.04 / kg (41,87%) and the value-added marketing process was Rp. 2.310.41 / bottle (33,01%) on manufacturers that sell products directly to consumers, amounting to Rp. 310,41 / bottle (6,21%) at a manufacturers that sell their products to wholesalers and retailers for Rp.1.805 / bottle (25,79%) on the wholesaler, and Rp. 1.820 / bottle (20,22%) at a retailer that is used by the wholesaler, Rp. 1.750 / bottle (25%) at a retailer by manufacturers, for soy milk products of regular soybean (imported), the value-added processing process Rp. 41.091,25 / kg (50,53%) and added value marketing process Rp. 1.870,38 / bottle (34,01%) on manufacturers that sell their products directly to consumers at Rp. 870,38 / bottle (19,34%) at a manufacturers that sell their products to wholesalers and retailers, Rp. 2.160 / bottle (33,23%) on the wholesaler, Rp. 960 / bottle (12,8%) on a retailer used by wholesalers, amounting to Rp. 980 / bottle (16,33%) on the two retailers that are used by the manufacturers. Marketing distribution channels of soy milk products in Denpasar either edamame soybean or usual soybean (imported) used the following channels: (1a) Manufacturer --Wholesaler - retailers - consumers; (1b) Manufacturer - Wholesaler - Consumers; (2) Manufacturer - Retailer - Consumer; and (3) Manufacturer - Consumer. Keywords: Soybean Milk, Added Value Analysis, Distribution Channels
Keywords: 134,